Antioxidant Activity In Combination Extract of Acorus Calamus L. (Dlingu) and Allium Sativum (Garlic) - Pramita Laksitarahmi Isrianto; Putu Oky Ari Tania (Hasanuddin University, 2019)
One of the efforts to optimize the utilization of natural materials that is used them as medicinal plants, including Dlingu (Acorus calamus L.) and Garlic (Allium sativum) which have the potential as antioxidants. This study aims to determine the effectiveness of a combination extract of Acorus calamus L. (Dlingu) and Allium sativum (Garlic) on antioxidant activity. This research is an experimental research which is the test of antioxidant content and antioxidant activity test with 5 series of concentrations and 4 times of repetition. The research materials, namely dlingu stem and single clove garlic tubers were extracted, phytochemical screening was carried out and then antiradical free IC50 was determined. Based on the test results of the chemical extract of dligu and single clove garlic, the highest content was alkaloid 5.16%, tannin 4.05%, saponin 3.01%, and flavonoid 2.18%. The test results of the chemical antioxidant activity of extracts dligu and single clove garlic contain IC50 values of 17.062 ppm, including a very strong class of antioxidants.Keywords: antioxidant, Dlingu, Single Clove (Male) Garlic.